THE ROLE OF NATURAL SCIENCE IN THE DEVELOPMENT OF SCIENTIFIC THOUGHT: COMPARISON OF EMPIRICAL AND THEORETICAL KNOWLEDGE - Khayitov , Ergash; Egamberdiyeva , Nargiza (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article discusses the role of natural science in the formation of scientific thinking in students, the interrelationship of empirical and theoretical knowledge, as well as the tasks given in Part II of Grade 2 and the skills to complete them, as well as the methods of applying new methods on this topic in practice.